1997
DOI: 10.1093/humrep/12.7.1440
|View full text |Cite
|
Sign up to set email alerts
|

How effective is patient-controlled analgesia? A randomized comparison of two protocols for pain relief during oocyte recovery

Abstract: Although the conventional method of pain relief during outpatient oocyte recovery involves physician-administered drugs, patient-controlled analgesia (PCA) offers an alternative technique with the potential to give women more control over peroperative analgesia. We conducted a prospective randomized study to compare the effect of fentanyl administered either through a PCA delivery system or by a physician. Thirty-nine women were randomized to PCA during egg collection while 42 were allocated to receive intermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 3 publications
0
10
0
2
Order By: Relevance
“…Interestingly, pain scores and satisfaction rates in both arms of this trial showed an improvement over those in a previous study comparing conventional intravenous with patient‐controlled intravenous analgesia [3] in which no anaesthetist was present at oocyte retrieval. Although not directly responsible for the administration of either the intravenous or the inhalational analgesia in this study, the presence of the anaesthetist may have been perceived as an added source of support for these women.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Interestingly, pain scores and satisfaction rates in both arms of this trial showed an improvement over those in a previous study comparing conventional intravenous with patient‐controlled intravenous analgesia [3] in which no anaesthetist was present at oocyte retrieval. Although not directly responsible for the administration of either the intravenous or the inhalational analgesia in this study, the presence of the anaesthetist may have been perceived as an added source of support for these women.…”
Section: Discussionmentioning
confidence: 62%
“…A previous study [3] demonstrated that 57% of women undergoing oocyte recovery using the conventional regimen of intermittent intravenous analgesia were ‘very satisfied’ with their pain relief. This study aimed to recruit a total of 112 women to yield 80% power of detecting, at the 5% significance level, a 25% difference (between 60 and 85%) in satisfaction rates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Th ese are paracervical block (Ng et al 2003), conscious sedation (Bhattacharya et al 1997), epidural (Martin et al 1999) and general anaesthesia (Gonen et al 1995). Since the fi rst RCT on the anaesthetic eff ect of acupuncture in IVF (Stener-Victorin et al 1999), further studies have shown that acupuncture can be used safely as an adjunct for pain relief during ultrasound-guided oocyte aspiration.…”
Section: Acupuncture For Pain Relief During Oocyte Aspiration In Ivfmentioning
confidence: 99%
“…L'efficacité antalgique de cette technique semble satisfaisante [26]. La pompe analgésique autocontrôlée (PCA) apporte elle aussi une bonne qualité de confort au cours de la ponction [27]. Nonobstant, la simple sédation et la pompe analgésique autocontrôlée peuvent provoquer une apnée ou une hypoxie, à l'occasion d'un surdosage morphinique.…”
Section: Risques Anesthésiquesunclassified